2005
DOI: 10.1007/s10198-005-0300-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of general practitioner records and patient self-report questionnaires for estimation of costs

Abstract: This study compared resource use data and estimated costs over a 12-month period, based on patient self-report questionnaires and general practitioner records. The level of agreement was measured by weighted kappa. Differences in total costs were plotted against mean total costs. Of 324 patients with complete GP records for the period only 85 (26.2%) had complete self-report data. The recorded number of contacts per patient was higher for patient questionnaires than GP records (17.20 vs. 12.64), and the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 13 publications
1
22
1
Order By: Relevance
“…There have been previous studies looking at the level of agreement or otherwise between these two methods. 57 We opted to ask REMCARE study participants to recall their type and frequency of contacts as a less intensive research method than interrogation of patient records. This triangulation substudy was designed to check the level of agreement or otherwise of participant recall with their GP records.…”
Section: A Comparison Of European Quality Of Life-5 Dimensions Scoresmentioning
confidence: 99%
“…There have been previous studies looking at the level of agreement or otherwise between these two methods. 57 We opted to ask REMCARE study participants to recall their type and frequency of contacts as a less intensive research method than interrogation of patient records. This triangulation substudy was designed to check the level of agreement or otherwise of participant recall with their GP records.…”
Section: A Comparison Of European Quality Of Life-5 Dimensions Scoresmentioning
confidence: 99%
“…Previous research has highlighted methodological limitations in the use of medical record reviews, including variations in accuracy or the amount of detail provided 20 and the risk of underestimating figures for consultations as not all are recorded in case notes. 7 However, one study comparing GP records and patient self-report questionnaires found similar figures for the mean number of consultations in both sources.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…7 However, one study comparing GP records and patient self-report questionnaires found similar figures for the mean number of consultations in both sources. 20 Additionally, a systematic review into computerised medical records revealed that the quality of the recording of consultations on such systems tended to be high. 21 The response rate for case record reviews was 86%.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…138 Costs Table 27 presents unadjusted costs incurred during the 25 weeks of follow-up. There were no statistically significant differences in categorised or total cost between treatment groups, although there was a tendency towards lower costs in the control group for all categories.…”
Section: Cost-effectivenessmentioning
confidence: 99%